Efektivitas Promosi Kesehatan dalam Meningkatkan Perilaku Hidup Bersih dan Sehat (PHBS) di Masyarakat - Sahabuddin, Sahabuddin; Sallo, Andi Kamal M.; Rosdiana, Rosdiana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Health promotion is the main strategy in efforts to improve public health. One indicator of its success is behavioral change towards Clean and Healthy Living Behavior (PHBS). This study aims to evaluate the effectiveness of health promotion on improving PHBS in the community. This research method uses a quantitative approach with a pre-experimental design using one group pre-test and post-test. The sample consisted of 100 heads of families who participated in health promotion activities in the work area of ​​Health Center X. The results showed an increase in knowledge, attitude, and PHBS practice scores after being given health promotion with a p value <0.05. Conclusion: Health promotion is effective in improving PHBS in the community. Sustainable health promotion interventions are needed as part of preventive and promotive strategies in primary health services.